Looking at library usability matching the concept from user’s experiences - Wan Bujang , Wan Abdul Rahman; Ibrahim, Korina (2012)
This study examined user’s current experiences about the usability of the libraries. Their views about the usability of the libraries may play an important role in the success of learning in general. Thus, this paper focuses on current views that reveal what users believe about the usability of existing libraries services and facilities offered. Historically, the quality of the library services have been described in terms of its collection and measured by the size of the library’s holding and various counts of its use. This traditional orientation no longer offers attainable goals for addressing successfully the community’s demands for information. Identifying new ways to conceive of quality and to monitor its attainment are current challenges for us as an academic library. While the business world has made great strides in focusing on customer service by studying customers’ needs and behaviors, libraries have tended to structure their holdings and services around what they believed was good for their customers or users. A syndrome named “librarians know best” required the librarians to transform the institution to a user-focused library. We are doing a survey by asking our users what they need and by listening carefully to what they say. Also continuously, monitoring what we are doing and asking what we could be doing better. The most important change we are making in our behavior is to evaluate our activities through our user’s eyes and ask ourselves what effect our actions will have on customer service and satisfaction.